The Impact of Brand Authenticity on Consumer Purchase Decisions in Digital Marketplaces: The Role of Brand Trust as a Mediator - Rachman, Intan Cahyani; Elvina, Elvina; Sa'diyah, Halimatus; Nursyidah, Nursyidah (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study aims to investigate how brand authenticity influences purchase decisions and its effect on brand trust within the digital marketplace. In addition, the research seeks to determine whether brand trust serves as a mediating factor in the relationship between brand authenticity and purchase decisions.Methodology: A quantitative research design was employed through a survey approach, gathering responses from 267 Indonesian consumers who had previously made purchases via digital platforms. The study used a purposive sampling technique, ensuring that participants met specific criteria relevant to the research focus. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect effects among the study constructs.Findings: The analysis revealed that brand authenticity has a significant positive effect on purchase decisions, reflected by a path coefficient of 0.995. Moreover, brand authenticity exerts a strong influence on brand trust (path coefficient = 0.863). While brand trust also positively impacts purchase decisions, its effect is comparatively smaller (path coefficient = 0.131). The mediation test further shows that brand trust partially mediates the link between brand authenticity and purchase decisions.Conclusion: This study shows how being genuine with a brand authenticity in building costumer trust and encouraging purchase decisions in the digital marketplace. The findings suggest that marketers should prioritize authenticity-driven branding strategies to reinforce consumer trust, promote brand loyalty, and enhance purchasing outcomes in competitive online environments.